Human papillomavirus (HPV) vaccine immunisation as an intervention programme for the prevention of cervical cancer and other similar HPV genotype-related diseases in South Africa: Some ethical and legal matters for consideration - Motopi, Lineo Mamphi (My University, 2014)
A new opportunity to reduce cervical cancer deaths as well as other HPV associated diseases arises from recently developed prophylactic vaccines. A large body of scientific literature concludes that the vaccines provide 100% protection against the oncogenic (high-risk) HPV types 16 and 18, which are responsible for about 70% of all cervical cancers in women. The vaccines also protect against infections with HPV 6 and 11, the cause of about 90% of genital warts (condylomataacuminata) in both males and females. South Africa is faced with uncertainties about how to implement a HPV vaccine immunisation programme aimed at the improvement of health in relation to the burden of disease caused by cervical cancer and related HPV-implicated diseases whilst struggling to provide the most basic of healthcare services in the midst of a HIV pandemic and a diminished base of key healthcare professionals. In such a context and relative to other priorities and the comparative benefits of different interventions, should, and if so why should South Africa invest in a HPV vaccine immunisation programme; likewise, if not, why not? In this research, report I will provide the main ethical and legal issues related to the implementation of a National HPV vaccine immunisation intervention programme. The research method used is a literature review of some ethical & legal issues in HPV vaccine immunisation analysing findings by way of critical thinking and moral reasoning. The outcomes of my research report suggest that South Africa is bound ethically and legally to provide HPV vaccine immunisation as an intervention to reduce the scourge of HPV infections, especially cervical cancer-based on the outcomes, I make recommendations concerning policy changes at the National level. These changes include interventions targeting the youth with an HPV vaccine immunisation programme included as one type of intervention.
Keywords: Papillomavirus Vaccines; Ethics, Medical